Antiphospholipid Antibody Syndrome and Infertility - Rodrigues, Vivian de Oliveira; Soligo, Adriana de Góes e Silva; Pannain, Gabriel Duque (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Antiphospholipid antibody syndrome (APS) is a systemic, autoimmune, prothrombotic disease characterized by persistent antiphospholipid antibodies (aPLs), thrombosis, recurrent abortion, complications during pregnancy, and occasionally thrombocytopenia. The objective of the present study was to review the pathophysiology of APS and its association with female infertility. A bibliographic review of articles of the past 20 years was performed at the PubMed, Scielo, and Bireme databases. Antiphospholipid antibody syndrome may be associated with primary infertility, interfering with endometrial decidualization and with decreased ovarian reserve. Antiphospholipid antibodies also have direct negative effects on placentation, when they bind to the trophoblast, reducing their capacity for invasion, and proinflammatory effects, such as complement activation and neutrophil recruitment, contributing to placental insufficiency, restricted intrauterine growth, and fetal loss. In relation to thrombosis, APS results in a diffuse thrombotic diathesis, with global and diffuse dysregulation of the homeostatic balance. Knowing the pathophysiology of APS, which is closely linked to female infertility, is essential for new therapeutic approaches, specialized in immunomodulation and inflammatory signaling pathways, to provide important advances in its treatment.
Keywords: antiphospholipid antibody syndrome; infertility; recurrent abortion; antiphospholipid antibody